2023
DOI: 10.1063/5.0172657
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating micromagnetic and atomistic simulations using multiple GPUs

Serban Lepadatu

Abstract: It is shown that micromagnetic and atomistic spin dynamics simulations can use multiple graphical processing units (GPUs) not only to reduce computation time but also to allow for a larger simulation size than is possible on a single GPU. While interactions that depend on neighboring spins, such as exchange interactions, may be implemented efficiently by transferring data between GPUs using halo regions or direct memory accesses, implementing the long-range demagnetizing interaction is the main difficulty in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…An example of such a simulation was given in Ref. [26]. The effect of the laser pulse is shown in Figure 3: the electron bath temperature increases rapidly on a fs timescale, with temperatures exceeding the Curie temperature.…”
Section: Ultrafast Magnetic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a simulation was given in Ref. [26]. The effect of the laser pulse is shown in Figure 3: the electron bath temperature increases rapidly on a fs timescale, with temperatures exceeding the Curie temperature.…”
Section: Ultrafast Magnetic Processesmentioning
confidence: 99%
“…In the latest version all GPU computations have been upgraded to allow multiple GPUs to be used simultaneously in order to reduce computation time, but also to allow for a larger simulation size than is possible on a single GPU [26], where it was shown that using a single workstation with 4 GPUs, atomistic spin dynamics simulations with up to 1 billion spins, and atomistic Monte Carlo simulations with up to 2 billion spins are possible, with a near-ideal performance scaling.…”
Section: Introductionmentioning
confidence: 99%